Eficácia dos programas psicoeducacionais na sobrecarga nos familiares cuidadores de pessoas com demência: revisão integrativa - Silva, Mafalda (2019)
Efficacy of psychoeducational programs in the overload of family caregivers of people with dementia: Integrative review ”BACKGROUND: Dementias have a major impact on the family, increas-ing the emotional overload of all household members, but mainly the caregiver and generating conflicts in the family dynamics. As such, the need to implement support programs for family caregivers emerges. Care-giver overload is understood as a set of physical, psychological, emotional, social and financial problems experienced by caregivers of patients with some type of impairment.AIM: To evaluate the effectiveness of psychoeducational programs in the overload of caregivers of people with dementia.METHODS: Integrative review of the literature on psychoeducational programs for caregivers, published between January 2010 and December 2015 in the PubMed and b-on databases, using the following keywords: “psychoeducation, dementia, caregiver, burden”.RESULTS: We analyzed 9 articles that evaluate the effects of the applica-tion of a psychoeducational program on the overload of family members of caregivers of patients with dementia. There is a substantial improvement in the well-being of caregivers; An increase in the acquisition of problem-solving strategies and stress-management techniques; Increase knowledge about resources in the community and how to deal with crisis situations in the different phases of the disease.CONCLUSION: The results suggest that the application of psychoeduca-tional programs in family caregivers of people with dementia has positive results in the caregiver’s overload and in the improvement of their well-being.